Diseases and human evolution - Barnes, Ethne (University of New Mexico Press, 2006)
"Recent interest in new diseases, such as HIV/AIDS and Ebola, and the resurgence of older diseases like tuberculosis has fostered questions about the history of human infectious diseases. How did they evolve? Where did they originate? What natural factors have stalled the progression of diseases or made them possible? How does a microorganism become a pathogen? How have infectious diseases changed through time? What can we do to control their occurrence?" "Ethne Barnes offers answers to these questions, using information from history and medicine as well as from anthropology. She focuses on changes in the patterns of human behavior through cultural evolution and how they have affected the development of human diseases." "Barnes offers general overviews of every variety of disease and their carriers, from insects and worms through rodent vectors to household pets and farm animals. She devotes whole chapters to major infectious diseases such as leprosy, syphilis, smallpox, and influenza. Other chapters concentrate on categories of diseases ("gut bugs," for example, including cholera, typhus, and salmonella). The final chapters cover diseases that have made headlines in recent years, among them mad cow disease, West Nile virus, and Lyme disease."--Jacket